THE EFFECT OF PURSED LIPS BREATHING IN INCREASING OXYGEN SATURATION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN INTERNAL WARD 2 OF THE GENERAL HOSPITAL OF DR. R. SOEDARSONO PASURUAN - Budiono, Budiono; Mustayah, Mustayah; Aindrianingsih, Aindrianingsih (Public Health of Indonesia, 2017)
Background: Chronic obstructive pulmonary disease is a leading cause of death and disability. Thus, the effort to reduce the symptoms, such as dyspnea is necessity. Pursed lip breathing is assumed increasing oxygen saturation.Objective: This study aims to determine the effect of pursed lips breathing in increasing oxygen saturation in patients with COPD in internal ward 2 of the General Hospital of Dr. R. Soedarsono Pasuruan on May 16 - June 30, 2017.Methods: This was a pre-experimental design with pre-posttest design. There were 24 patients with COPD selected using simple random sampling technique. Pulse oximetry (oximeter pulse fingertip) was used to measure oxygen saturation. Data were analyzed using Wilcoxon Sign Rank Test.Results: Findings showed p-value 0.000 (<0.05), which indicated that there was a statistically significant difference in oxygen saturation before and after pursed lips breathing.Conclusion: There was a significant effect of pursed lips breathing on oxygen saturation in patients with COPD in the internal ward 2 of the general hospital of Dr. R. Soedarsono Pasuruan. Thus, pursed lips breathing could be applied as a nursing intervention in patients with COPD.